2020
DOI: 10.1109/tmi.2019.2938028
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Crystal Timing Properties and Efficiencies for the Improvement of (Joint) Maximum-Likelihood Reconstructions in TOF-PET

Abstract: With increasing improvements in the time of flight (TOF) resolution of positron emission tomography (PET) scanners, an accurate model of the TOF measurements is becoming increasingly important. This work considers two parameters of the TOF kernel; the relative positioning of the timing data-bins and the timing resolution along each line of response (LOR). Similar to an existing data-driven method, we assume that any shifts of data-bins along lines of response can be modelled as differences between crystal timi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Moreover, shorter imaging time can greatly accelerate the examination time and reduce the pain of patients [ 4 ]. The performance of a PET system [ 5 , 6 , 7 , 8 , 9 ] directly depends on its components, which include a scintillation crystal, a photodetector, a readout circuit, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, shorter imaging time can greatly accelerate the examination time and reduce the pain of patients [ 4 ]. The performance of a PET system [ 5 , 6 , 7 , 8 , 9 ] directly depends on its components, which include a scintillation crystal, a photodetector, a readout circuit, etc.…”
Section: Introductionmentioning
confidence: 99%
“…With improvements in the TOF resolution of future scanners, accurate TOF-based calibrations will become increasingly important. It has been shown that compared to conventional MLEM reconstructions, joint estimation techniques are more sensitive to timing calibration errors (timing offsets and time resolution (Rezaei et al 2019)).…”
Section: Image Reconstruction and Joint Estimationmentioning
confidence: 99%
“…This underlines that precise knowledge of the TOF kernels is crucial for accurate TOF-MLEM reconstructions. Fortunately, data-driven ML techniques can be used to estimate a global TOF kernel width [139] or even an LOR-dependent correction factor for the TOF kernel width [140] in case the TOF resolution is LORdependent.…”
Section: A Tof-pet Reconstruction Basicsmentioning
confidence: 99%
“…Recently, deep learning techniques (e.g., convolutional neural networks) have been used to improve the quality of the attenuation images obtained from MLAA [ 157 ], [ 158 ]. Also, it was recently shown [ 139 ] that joint estimation of activity and attenuation is more sensitive to inaccuracies in the TOF kernel, such as the exact TOF resolution and possible coincidence timing offsets, indicating that the required precision in the TOF calibration and modeling needs to be improved for future systems with even better TOF resolution.…”
Section: Utilization Of Time Resolution In Pet Image Reconstructionmentioning
confidence: 99%